2011
DOI: 10.3354/cr01012
|View full text |Cite
|
Sign up to set email alerts
|

Summer mean temperature variation from 1710–2005 inferred from tree-ring data of the Baimang Snow Mountains, northwestern Yunnan, China

Abstract: The tree-ring chronologies of Abies georgei Orr were developed for 3 sites at different elevations: the southern (2750 m), middle (3050 m), and northern (3400 m) parts of the Baimang Snow Mountains in northwestern Yunnan Province, China. The climate-growth response analysis indicated that trees at different elevations respond differently to environmental changes. The radial growth of trees found at the middle and high elevation sites was determined by temperature variables (mean, maximum, and minimum temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
9
14
0
Order By: Relevance
“…2) is a widely observed cold period. This cold period from the late 18th to the mid-19th century is also seen in other proxy records from South-east Tibet (Shi et al, 2012), west Sichuan (Br€ auning & Mantwill, 2004) and north-west Yunnan (Li et al, 2011(Li et al, , 2012. 1810-1820 was the coldest period during the last 240 years, around 0.5°C below the average temperature, with another cooling period around 1840 (Liang et al, 2009).…”
Section: Climate Forcing and Community Structuresupporting
confidence: 74%
“…2) is a widely observed cold period. This cold period from the late 18th to the mid-19th century is also seen in other proxy records from South-east Tibet (Shi et al, 2012), west Sichuan (Br€ auning & Mantwill, 2004) and north-west Yunnan (Li et al, 2011(Li et al, , 2012. 1810-1820 was the coldest period during the last 240 years, around 0.5°C below the average temperature, with another cooling period around 1840 (Liang et al, 2009).…”
Section: Climate Forcing and Community Structuresupporting
confidence: 74%
“…This positive relationship may be due to the relatively short distance between the two sampling sites. Our reconstruction also preserves a marked resemblance of decadal‐scale temperature variation with summer temperature reconstruction for northwestern Yunnan during the period from 1840–2001 ( r = 0.457, P < 0.01) (Li et al , ) and summer temperature reconstruction for the source region of the Yangtze River on the Tibetan Plateau during the period from 1840 to 2002 ( r = 0.467, P < 0.01) (Liang et al , ). The comparisons described above are indicative of the capacity of the reconstruction in this study to capture temperature signal over a well‐defined spatial domain.…”
Section: Discussionsupporting
confidence: 58%
“…A similar climatic response has been reported for the timberline forests on the eastern and northeastern TP (Shao and Fan, 1999;Bräuning, 2006;Liu et al, 2007;Liang, 2006Liang, , 2009). In previous studies, T min has been found to constrain radial growth in the TP (Gou et al, 2007a;Li et al, 2011b;Liang et al, 2008;Liang et al, 2010;Lv and Zhang, 2013). Even though the cambium tissues of trees are dormant in winter and early spring, the phloem sap may have freezing damages when temperatures are low during this period (Kimmins, 1987).…”
Section: Climatic Implications Of the Upper Treeline Chronologiesmentioning
confidence: 99%